68 Exploring Subconscious Bias: How Implicit Biases Can Affect Accessibility to Healthcare. (28th February 2022) - Ranford, D.; Miu, K.; Surda, P.
Abstract: Aim: Implicit biases involve associations outside conscious awareness that lead to a negative evaluation of a person on the basis of irrelevant characteristics such as race or gender. This article reviews healthcare professional's display of implicit bias towards patients in a tertiary centre. Method: We retrospectively analysed a database of 285 patients who missed surgical outpatient appointments at a London tertiary hospital. Judges were asked to categorise all 285 patients into predefined ethnic categories: White British vs Black, Asian and Minority Ethnic vs White Non-British after reading the patient's names. Results: In the group where ethnicity was defined based on assessed origin of names, we report significant difference in discharge rates between White British vs Non-White British groups (34 vs 48%). There was also significant difference between White British vs Black, Asian and Minority Ethnic group (34% vs 57%). Discharge rates between males and females did not differ. Conclusions: Clinicians are more likely to provide patients with another opportunity to attend an outpatient clinic after missing a booked appointment based on the patient having a perceived ethnicity of White British, whether deliberate or not. This study shows a bias of accessibility in healthcare dependent on ethnicity with greater flexibility given to White British patients.